Calculation Algorithm for Squeeze Film Damper. (2015) - Novikov, D.K.; Diligensky, D.S.
Abstract: This work discusses a number of issues related to the selection of the squeeze film damper type. Here has been performed the analysis of works dedicated to this issue and it has been shown that today there is a large variety of damper designs. Therefore, the method allowing reasonably select the type of dampers and their parameters is required. It contains the methodology for designing such dampers consisting of the stages of parametrical optimization for the "rotor-damper" system, damper structural optimization and selection of optimal parameters of dampers from selected type.